Advances in Communication of Design Proceedings of the AHFE 2017 International Conference on Human Factors in Communication of Design, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA (Advances in Intelligent Systems and Computing,, 2018)
This book focuses on the emerging role of human factors in understanding, communicating with and engaging users. It reports on innovative approaches, with a special emphasis to visuals cues, such as new typographies, geometries and graphics for mobile and computer interfaces. The book also cover topics of image and video processing, user-focused data compression, generative visuals, computational photography, and interactive design. Further topics include creative and empathetic design, human touch in digital graphics and experiential graphics. Based on the AHFE 2017 International Conference on Human Factors in Communication of Design, held on July 17-21, 2017, in Los Angeles, California, USA, this book reports on new findings, best-practices and case studies, providing readers with a fresh perspective and novel insights into the applications of human factors for enriching communication of design to users.